Perkembangan Digitalisasi Hadis: Analisis Ensiklopedia Hadits 9 Imam Karya Lidwa Pusaka - Burhani, Luthfia Shifaul Amanah (Journal of Hadith Studies, 2021)
The study of hadith continues to evolve, particularly in response to the rapid advancement of the digital age and technological innovation. This development is evident in the increasingly accessible methods of retrieving hadith, which were once obtained through manual efforts but are now facilitated by various digital applications and software. Mausu'ah al-Hadith al-Sharif and the digital library Maktabah Syamilah are among the most comprehensive tools. Additionally, several hadith applications featuring Indonesian language support have emerged, one of which is the Encyclopedia of Hadith: The Nine Imams’ Collection, developed by Lidwa Pustaka in collaboration with Saltanera Teknologi. This article adopts a descriptive approach grounded in literature review to explore the use of such applications, focusing on analyses drawn from recent scholarly articles. One key finding highlights that the Encyclopedia of Hadith: The Nine Imams’ Collection provides considerable convenience in hadith authentication (takhrij) and is widely used as a digital reference in both da’wah and educational contexts. Nonetheless, the ease of access also carries potential risks, particularly concerning the authenticity of hadiths disseminated through digital platforms. Thus, it is crucial to foster a strong understanding of hadith and its sciences, instill values of honesty and integrity in hadith research and dissemination, and promote the use of credible applications such as the Hadith Encyclopedia as foundational tools in digital hadith studies